The reason analysis of the overburden rock dumps deformation - Ananenko Elena (EDP Sciences, 2021)
Due to the deficiency of areas for dump facilities, mining enterprises form dumps of a large height, or locate them in places unfavorable from the stability point of view. In this regard, cases of the dump areas landslides have become more frequent. Herein there are examples of the actual deformations, causes of their occurrence, as well as preventive measures. Experience of the field surveying observations and analysis of the dump landslide causes confirm that accidents could be prevented by timely substantiating of safety criteria for the stress strain status of the dumps and creating methodology for surveying monitoring, depending on a type of the overburden rock.